Therapists’ Views of Mechanisms of Change in Psychotherapy: A Mixed-Method Approach - Tzur Bitan, Dana; Shalev, Shani; Abayed, Shiran (Frontiers in Psychology, 2022)
The question of what works in psychotherapy has been a subject of debate in recent years, occupying both clinicians and researchers. In this study we aimed to assess the current perspectives held by clinicians regarding the processes which produce change in psychotherapy, as well as predictors of specific views. Licensed therapists (n = 107), consisting mainly of psychodynamically and integratively oriented psychologists, were asked to write in their own words what they think works in psychotherapy. The Braun and Clarke (2006) approach to thematic analysis was employed in order to assess the main mechanisms of change as perceived by the therapists. Differences in the prevalence of specific themes were assessed using Friedman and Wilcoxon signed-rank tests. Univariate logistic regressions were employed to assess the factors predicting the probability of reporting a specific mechanism of change. The results indicated that the therapeutic bond was the most highly reported mechanism of change, followed by theory-driven mechanisms of change, therapist characteristics, therapist professionalism, and client motivation. Male therapists were more likely to indicate professionalism as a mechanism of change compared to female therapists. Higher education was associated with lower reports of therapists’ characteristics as mechanisms of change. These results suggest that therapists acknowledge the importance of the working alliance, and that the perception of the mechanism of change is associated with various factors which comprise therapist orientation. Limitations and directions for future research are discussed.